Pedampingan Pengembangan Pembelajaran Sains Anak Usia Dini - Ida Ayu Made Yuni Andari; Ni Made Dwi Utari; Ni Made Frescillia Atika; Ni Putu Ary Wardani; Ida Ayu Putu Swarikanti (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
Science is a type of learning that is very important to help young children in their development process, both cognitive and physical motor development. Educating children from an early age is the main task and priority for every parent, teacher, institution or government. Maximizing early childhood education must integrate all aspects of the child's environment that have a vision and mission in providing educational services. Descriptive qualitative research method with data collection techniques documentation studies, interviews and observations. Science learning is a type of learning that is carried out in kindergarten or early childhood in order to help provide a stimulus for every early childhood development. Science learning is applied in groups such as making fruit satay, outting classes, introducing the solar system.